Evaluation of the knowledge of pregnant women about the relationship between oral diseases and pregnancy complications - Carmem Dolores de Sá Catão; Thaissa de Amorim Gomes; Rachel Queiroz Ferreira Rodrigues; Renata de Souza Coelho Soares
INTRODUCTION: Chronic persistent low-level infection in pregnant women, such as periodontal disease (PD) may impair maternal-fetal unit, since the infectious process induces the release of chemical mediators involved in the process of prematurity. OBJECTIVE: To assess the knowledge of mothers as regards the relationship between oral diseases and pregnancy complications. METHOD: A cross-sectional epidemiological study was conducted with 104 pregnant women indexed in the Primary Care Information System (SIAB), in the Family Health Strategies (FHS), using a structured questionnaire. Data were recorded in SPSS and analyzed using descriptive and inferential statistics, considering a significance level of 5%. RESULT: Most patients (64.4%) were domestic workers, (48.1%) aged 24 to 34 years, (55.8%) showed complete the 2nd grade and incomplete high school education, and (49%) were primiparous. Among the participants, 76% were unaware of the relationship between oral disease, prematurity and giving birth to low birth weight babies. Statistically significant association was found between: educational level and knowledge about prenatal dental care (p = 0.012); since it was shown that 90.4% ignored the existence of this activity and 65.4% had never received information about the care of baby's oral hygiene (p = 0.003). CONCLUSION: Most women were unaware of the relationship of PD with prematurity, and showed lack of information about the care of mother and baby oral hygiene, highlighting the need for greater integration between the dental surgeon and other primary care professionals to promote oral health care of pregnant women and reduce the ratio of PD with pregnancy complications.